Law & Order in Digital Forensics: A Decade of Reproducibility Insights - Najmy Amien, Muhammad; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article presents a comprehensive dataset curated from Lens.org, comprising 185 journal articles focused on the intersection of "Digital Forensic" and "Reproducibility of Results" within the field of Law. The dataset covers a ten-year span from 2012 to 2022, facilitating research on digital forensic investigations and the replicability of findings in a legal context. This resource serves to streamline data retrieval for researchers interested in this specific domain, aiding in the advancement of knowledge and experimental developments related to digital forensic research and its reproducibility. Highlights : Data Content: A curated dataset of 185 journal articles, spanning 2012-2022, at the intersection of digital forensics and reproducibility in law. Research Facilitation: Simplifying data retrieval for researchers, enhancing the ease of investigating digital forensic practices and their replicability in legal contexts. Knowledge Advancement: This dataset empowers further insights and experimental developments within the digital forensic domain. Keywords: Digital Forensic Research, Reproducibility of Results, Legal Implications, Data Article, Ten-Year Dataset